Marketing research essentials - McDaniel, Carl D. 1941-; Gates, Roger (Wiley, 2016)
" In the 12th edition of Marketing Research, McDaniel and Gates continue to share their industry experience to teach students how to make critical business decisions through the study of market research. The authors' practical, applications-based approach features real data, real people, and real research, to prepare students to conduct and use market research for future careers in business. Co-author Roger Gates, President of DSS Research, infuses the text with a practitioners perspective, helping students learn how to use marketing research through a practical presentation of both theory and practice "...